2020
DOI: 10.1021/acsomega.0c03270
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Isolation of Cytotoxic Sesquiterpene Lactones from Eupatorium fortunei by the NMR Annotation Tool, SMART 2.0

Abstract: Small Molecular Accurate Recognition Technology (SMART 2.0) has recently been introduced as a NMR-based machine learning tool for the discovery and characterization of natural products. We attempted targeted isolation of sesquiterpene lactones from Eupatorium fortunei with the aid of structural annotation by SMART 2.0 and chemical profiling. Eight germacrene-type ( 1–7 and 10 ) and two eudesmane-type sesquiterpene lactones ( 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Despite the majority of the computational screening approaches using ML algorithms lacking experimental validations, we have some interesting successful studies that aimed to find and characterize novel natural products with experimentally validated biological activity (Rupp et al, 2010 ; Zhang et al, 2017 ; Nocedo-Mena et al, 2019 ; Patsilinakos et al, 2019 ; Lee et al, 2020 ; Liu et al, 2020 ). Recently, Reher et al reported on the SMART 2.0, an NMR-based machine learning tool designed for the discovery and characterization of natural products.…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the majority of the computational screening approaches using ML algorithms lacking experimental validations, we have some interesting successful studies that aimed to find and characterize novel natural products with experimentally validated biological activity (Rupp et al, 2010 ; Zhang et al, 2017 ; Nocedo-Mena et al, 2019 ; Patsilinakos et al, 2019 ; Lee et al, 2020 ; Liu et al, 2020 ). Recently, Reher et al reported on the SMART 2.0, an NMR-based machine learning tool designed for the discovery and characterization of natural products.…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%
“…Similarly, Lee et al applied SMART 2.0 to prioritize the isolation and characterization of sesquiterpene lactones from the Eupatorium fortune plant. The isolated natural compounds were experimentally tested against five cancer cell lines and exhibited cytotoxic activities (Lee et al, 2020 ).…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%
“…Three germacranolide sesquiterpene lactones, (macrocephalides A-C) 74-76(Figure 5) were isolated from Eupatorium macrocephalum. 74 and 75 showed potent cytotoxicity (Lee et al, 2020). However, 76 showed moderate cytotoxicity in various tumour cell lines (Yang et al, 2019).…”
Section: Genus Eupatoriummentioning
confidence: 96%
“…The final R 1 was 0.0358 (I > 2σ(I)) and wR 2 was 0.0936. Flack parameter: −0.01 (10). Crystallographic data for 1 have been deposited at the Cambridge Crystallographic Data Centre as deposit no.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…C 17 H 24 O 6 : M = 324.36 g/mol, orthorhombic, space group P2 1 2 1 2 1 (no. 19), a = 6.64130 (10) Å, b = 14.8419(3) Å, c = 16.7613(3) Å, α = 90°, β = 90°, γ = 90°, V = 1652.15(5) Å 3 , Z = 4, T = 140 K, μ(Cu Kα) = 0.815 mm −1 , D calc = 1.304 g/cm 3 , 23 113 reflections measured (7.956°≤ 2σ ≤ 149.016°), 3375 unique (R int = 0.0380, R sigma = 0.0212), which were used in all calculations. The final R 1 was 0.0282 (I > 2σ(I)) and wR 2 was 0.0722.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%